The relationship between chronic air pollution exposure, neighborhood environmental vulnerability, and adverse COVID-19 morbidities among hospitalized New York City residents - Sneha Kannoth; Cong Zhang; Mehr Shafiq; Sandra S. Albrecht; Alexander Azan; Earle C. Chambers; Min Qian; Perry E. Sheffield; Azure Thompson; Jennifer A. Woo Baidal; Stephanie Lovinsky-Desir; Jeanette A. Stingone (Environment International)
Introduction: Communities disproportionately burdened by adverse neighborhood-level social and structural factors may experience greater vulnerability to environmental exposures, contributing to health inequities, including adverse COVID-19. We assessed the effects of chronic air pollution on COVID-19 morbidities in NYC and examined whether these effects varied by neighborhood-level vulnerability. Methods: We used NYC COVID-19 hospitalization records (3/1/2020–2/28/2021) and conducted analyses in the full sample and within hospital catchment. Chronic air pollution (particulate matter (PM2.5), nitrogen dioxide (NO2), black carbon (BC), ozone (O3)) was assigned using residential ZIP Code (NYC Community Air Survey; 2009–2019). Modified Poisson regression estimated risk of acute respiratory distress syndrome (ARDS), pneumonia, ventilation, and dialysis, and Cox regression estimated risk of discharge, adjusting for age, sex, BMI, smoking, asthma, diabetes, and hypertension. We assessed effect modification by neighborhood-level environmental vulnerability index (NEVI) tertiles. Results: From March to June 2020 (within hospital catchment), adjusted estimates generally suggest greater chronic NO2, PM2.5, and BC was associated with increased risk of ARDS, pneumonia, and dialysis, and not associated with discharge and ventilation; inverse estimates found for chronic O3. Relationships between air pollution and adverse COVID-19 were generally stronger among those with greater neighborhood environmental vulnerability. For example, chronic NO2 and pneumonia’s relationship was stronger in individuals within higher NEVI tertiles (T1: aRR: 1.13, 95%CI: 1.02–1.25; T2: aRR: 2.11, 95%CI: 1.73–2.56; T3: aRR: 6.36, 95%CI: 4.71–8.60). Discussion: Differences in neighborhood-level social and structural factors contribute to unequal health burdens associated with air pollution. Public health resources targeted toward neighborhoods with greater environmental vulnerability can encourage population-level pandemic preparedness.